2023
DOI: 10.1096/fj.202201784r
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid exposure modifies the miRNA profile of sperm in the guinea pig: Implications for intergenerational transmission

Abstract: Approximately 1%-3% of the adult population are treated with synthetic glucocorticoids (sGCs) for a variety of conditions. Studies have demonstrated that adversities experienced by males prior to conception may lead to abnormal neuroendocrine function and behaviors in offspring and that epigenetic factors including microRNA (miRNA) within sperm may be responsible for driving these effects. However, it remains unclear where in the epididymis sperm miRNA changes are occurring. Here, we hypothesized that sGC expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Our studies suggest that the intergenerational effects of prenatal Beta (F0 pregnancy) on sperm miRNA levels may be mediated primarily in the epididymis and involve alterations in the epididymal epithelial cells and epididymosomes. In this regard, we have recently shown that the miRNA profile of cauda sperm in the epididymis is influenced following sGC exposure in adult males (Casciaro et al., 2023). These findings suggest that sGCs target the GR in the epididymis during sperm maturation rather than the testes during spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies suggest that the intergenerational effects of prenatal Beta (F0 pregnancy) on sperm miRNA levels may be mediated primarily in the epididymis and involve alterations in the epididymal epithelial cells and epididymosomes. In this regard, we have recently shown that the miRNA profile of cauda sperm in the epididymis is influenced following sGC exposure in adult males (Casciaro et al., 2023). These findings suggest that sGCs target the GR in the epididymis during sperm maturation rather than the testes during spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The Matthews research team recently demonstrated in another study that glucocorticoids can indeed impact sperm miRNA directly. Casciaro et al (2023) provided adult male guineapigs sGC daily throughout the period of spermatogenesis and demonstrated altered miRNA profiles within sperm from the cauda of the epididymis. Hamada et al also highlighted an important association between miR-125b, which was altered across generations in the sperm, and its target gene, Itga8, in the prefrontal cortex of F 1 and F 2 female offspring.…”
mentioning
confidence: 99%
“…Casciaro et al. (2023) provided adult male guineapigs sGC daily throughout the period of spermatogenesis and demonstrated altered miRNA profiles within sperm from the cauda of the epididymis.…”
mentioning
confidence: 99%